Injury incidence, prevalence and severity in high-level male youth football: A systematic review - Jones, S.; Almousa, S.; Gibb, A.; Allamby, N.; Mullen, R.; Andersen, T. A.; Williams, M. (Sports Medicine, 2019)
Background: At a young age, high-level youth footballers enter structured practice where they engage in regular training and matches. The academy system is considered fundamental to a young footballer`s tactical, technical and physical development. Yet, with regular training and matches, high-level youth footballers may be exposed to the risk of injury. Objective: This systematic review analyses and summarises published scientific information on high-level youth football injury characteristics and calculates the risk of them sustaining an injury over the course of a typical season. Methods: The search was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Of the 1346 studies found, 23 fulfilled the inclusion criteria. Results: Quality assurance scores for the selected research articles ranged between two and five out of eight. A high degree of heterogeneity between studies was observed. The probability of sustaining a time-loss injury during a high-level youth season ranged between < 1% and 96% for under 9- to under 16-year age groups and 50% and 91% for under 18- to under 21-year age groups. Pooled estimates for total (training and match) incidence per 1000 h was 5.8 for youth players aged under 9 to under 21 years, 7.9 for older players (under 17-under 21 years) and 3.7 for younger aged players (under 9-under 16 years). Training injury incidence rate ranged from 0.69 to 7.9 per 1000 h for all age groups in youth football. Match injury incidence rate for high-level youth players ranged from 0.4 to 80.0 per 1000 h. Close to one-fifth (18%) of all high-level youth football injuries were classified as severe and required > 28 days recovery time. Muscle strain injury accounted for 37% of all injuries reported in youth football. High probabilities (> 90%) of sustaining a time-loss injury over one typical high-level football season were found. Conclusion: High-level youth players lose large portions of the seasonal development to injury, with players seemingly suffering long absences from training and matches, consequently affecting health and well-being and possibly burdening club/parental finances and healthcare systems.